(untitled) (Research, Society and Development, 2021)
This randomized clinical trial aimed to evaluate the endodontic retreatment techniques influence using reciprocating files and ultrasonic inserts in relation to the incidence, intensity, and postoperative pain duration. Forty-six patients were randomly assigned into two groups: Reciprocant files (RC group); or the Clearsonic Ultrasonic Insert (CL group;). Participants were asked to report the incidence, duration, and postoperative pain intensity using a visual analog scale (VAS) at 24, 48 and 72 h after retreatment. Fisher’s exact test was used to compare the two methods used regarding postoperative pain. The Mann-Whitney test was used to compare pain intensity, and Friedman’s test was used to assess the time effect on pain intensity. Finally, ordinal logistic regression analysis was used to assess the odds ratio for pain occurrence at a significance level of 5%. The postoperative pain incidence was significantly lower in the CL group in all experimental periods. Comparing the two techniques, pain intensity was significantly lower in the CL group after 24 and 48 h. For the RC group, pain intensity was significantly greater at 24 h compared with the other periods. The technique used in endodontic retreatment can influence postoperative pain.